Detection and Transstadial Passage of Babesia Species and Borrelia burgdorferi Sensu Lato in Ticks Collected from Avian and Mammalian Hosts in Canada - John D. Scott; Kerry L. Clark; Nikki M. Coble; Taylor R. Ballantyne (Healthcare, 2019)
Lyme disease and human babesiosis are the most common tick-borne zoonoses in the Temperate Zone of North America. The number of infected patients has continued to rise globally, and these zoonoses pose a major healthcare threat. This tick-host-pathogen study was conducted to test for infectious microbes associated with Lyme disease and human babesiosis in Canada. Using the flagellin (flaB) gene, three members of the Borrelia burgdorferi sensu lato (Bbsl) complex were detected, namely a Borrelia lanei-like spirochete, Borrelia burgdorferi sensu stricto (Bbss), and a distinct strain that may represent a separate Bbsl genospecies. This novel Bbsl strain was detected in a mouse tick, Ixodes muris, collected from a House Wren, Troglodytes aedon, in Quebec during the southward fall migration. The presence of Bbsl in bird-feeding larvae of I. muris suggests reservoir competency in three passerines (i.e., Common Yellowthroat, House Wren, Magnolia Warbler). Based on the 18S ribosomal RNA (rRNA) gene, three Babesia species (i.e., Babesia divergens-like, Babesia microti, Babesia odocoilei) were detected in field-collected ticks. Not only was B. odocoilei found in songbird-derived ticks, this piroplasm was apparent in adult questing blacklegged ticks, Ixodes scapularis, in southern Canada. By allowing live, engorged ticks to molt, we confirm the transstadial passage of Bbsl in I. muris and B. odocoilei in I. scapularis. Bbss and Babesia microti were detected concurrently in a groundhog tick, Ixodes cookei, in Western Ontario. In Alberta, a winter tick, Dermacentor albipictus, which was collected from a moose, Alces alces, tested positive for Bbss. Notably, a B. divergens-like piroplasm was detected in a rabbit tick, Haemaphysalis leporispalustris, collected from an eastern cottontail in southern Manitoba; this Babesia species is a first-time discovery in Canada. This rabbit tick was also co-infected with Borrelia lanei-like spirochetes, which constitutes a first in Canada. Overall, five ticks were concurrently infected with ...